ANALISIS PENGENDALIAN RISIKO PADA DOKUMEN KREDIT PEMILIKAN RUMAH (KPR) UNTUK MENCEGAH FRAUD DAN HUMAN ERROR DI BANK TABUNGAN NEGARA (PERSERO). TBK KC MAGELANG - Pratama, Muhammad Rizqy; Musthafa, Musthafa (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze risk control on mortgage documents to prevent fraud and human error at BTN Magelang Branch Office. The research method used is descriptive with a qualitative approach through interviews, observation, and documentation. The results showed that the biggest risk factor in the document section was fraud and human error. Fraud committed by officers or document staff who use debtor data or documents used for personal gain without the knowledge of the agency and the debtor, causing losses to all parties. Human errors that occur in the document section often occur because of poor document management so that debtor documents will experience mixing with other debtor documents, document damage, and loss of debtor documents.